The Anfu Parliament in Republican China. The life and death of a failed single-party state, 1918–20. (2nd January 2022) - Quan, Yan; Leung, Ernest Ming-tak
ABSTRACT: The Anfu Club, which governed China in 1918–20, has often been seen as a factionalist grouping of corrupt and incompetent politicians handpicked by the military and kept afloat by Japanese loans and state subsidies. The fact that they had achieved domination in parliament through vote-rigging was often seen as sufficient to write off their achievements. This article argues that Anfu, which was East Asia's first single-party state, oversaw one of the most accomplished periods in the legislative history of the Republic of China. It was a highly efficient legislature which passed much-needed laws, thanks to rigorous inner-party discipline. It had an internationalist diplomatic line and it hoped to participate in planning for the post-war international order. Due to a lack of consensus in the military over how a single-party state should be run, however, Anfu found itself abused and scapegoated frequently and fought back using constitutional means, impeaching officials including the Premier, slashing the military budget by 20 per cent, and demanding cabinet appointments appropriate to its status as the parliamentary majority. Eventually this caused a rupture between it and its rival forces in the military, leading to the 1920 civil war that precipitated Anfu's collapse.